STUDENT ACADEMIC PERFORMANCE: DOES A STUDENT-SPECIFIC STARTING LINE MATTER? - Sek, Ngo Chi; Mok, Vincent; Leung, Man; Li, Zongzhang (PUPIL: International Journal of Teaching, Education and Learning, 2018)
This study investigates the effects of student time allocation on the academic performance of undergraduate students in Hong Kong by using data envelopment analysis approach. To determine the factors affecting students’ educational productive efficiency, we analyze whether a student-specific starting line (qipaoxian, in Chinese pinyin) matters. The pre-university student-specific attributes are identified as a starting line that comprises pre-university study ability, motivation, and parents’ educational background. Results suggest that most starting line components have insignificant effects on university students’ education efficiency, except students’ self-motivation in terms of ambition to earn more money and students’ pre-university English language proficiency. Research findings generate policy implications to the educational institutions on developmental perspectives. For example, universities in Hong Kong can consider offering more intense English language courses to students with relatively lower English language proficiency. In doing so, students’ education efficiency can be enhanced.